CULTURAL WORKS POLITICS OF IVAN MAZEPA - Макаровський, І. П. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article revealed the role of Hetman Ivan Mazepa in the development of Ukrainian culture and of the beginning of the XVII-XVIII century covered national political aspect of the state and direction of its cultural politics, financial support national original church building, education, science, art, literature, architecture, music (a synthesis of Western Europe Baroque forms and local Ukrainian artistic tradition)